Influence of hiring, selection process and safety training on lightning safety performance in Iranian manufacturing companies - Hajikhani M.; Izadi M.; Kadir M.Z.A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Employment; Lightning protection; Manufacture; Safety engineering; Factors of safeties; Hiring and selection; Iranian companies; Manufacturing companies; Organizational levels; Safety performance; Safety training; Lightning